Guzarish-i kutahi az hashtumin siminar-i Junbish-i Mustaqqil-i Zanan-i Irani dar Kharij az Kishvar : (Junbish-i Mustaqqil-i Zanan-i Irani dar Kharij az Kishvar)
'A short report of the eighth seminar of Independent Movement of Iranian women's abroad'.